Participatory rural appraisal handbook : conducting PRAs in Kenya. - Center for International Development and Environment (Washington, DC : World Resources Institute, Center for International Development and Environment, 1990)
This book provides insight into dealings and behavioural nature in rural communities.
oo 10/04/2019
Loans
Keywords: Rural development; Water resources; Agriculture